2015
DOI: 10.1111/ppa.12370
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of virulence shifts and population genetic changes of Pseudoperonospora cubensis in the Czech Republic

Abstract: Pseudoperonospora cubensis is an oomycete pathogen causing downy mildew disease on a variety of Cucurbitaceae, and has recently re‐emerged as a destructive disease on crops in this family, mainly on cucumber and squash. Multilocus sequence analysis (MLSA) of four mitochondrial and two nuclear DNA regions was used to detect changes in the genetic structure of P. cubensis populations occurring in the Czech Republic that might be associated with recently reported shifts in virulence. The analysed sample set conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…Previous studies using multilocus phylogenetic analyses of variation in cox2 , ypt1, and nrITS in several similar strains also provided evidence of two clades within P. cubensis (Kitner et al., ; Runge et al., ). Evolutionary lineages I and II identified in the current study were found to be congruent with clades 1 and 2 (Runge et al., ), respectively, based on a phylogenetic analysis of sequence data obtained from NCBI (Figure ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies using multilocus phylogenetic analyses of variation in cox2 , ypt1, and nrITS in several similar strains also provided evidence of two clades within P. cubensis (Kitner et al., ; Runge et al., ). Evolutionary lineages I and II identified in the current study were found to be congruent with clades 1 and 2 (Runge et al., ), respectively, based on a phylogenetic analysis of sequence data obtained from NCBI (Figure ).…”
Section: Discussionmentioning
confidence: 85%
“…The evolutionary origin of P. cubensis and the relatedness to its sister species, P. humuli that infects hop, have been widely investigated (Choi, Hong, & Shin, ; Göker, Voglmayr, Riethmüller, & Oberwinkler, ; Kitner et al., ; Mitchell, Ocamb, Grünwald, Mancino, & Gent, ; Runge & Thines, ; Runge et al., ). Choi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(), and also affects population genetics of cucurbit downy mildew, Pseudoperonospora cubensis (Lebeda & Cohen, ; Kitner et al ., ). The majority of the borders of the Czech Republic are natural mountain barriers, except for the southeastern region, which is relatively open to air currents from southern Europe, thus representing the main potential source of genetic material at the beginning of the cucurbit growing season (May–June) (Kitner et al ., ). During the main growing season (July–August), infection by propagules from all neighbouring European countries could also occur.…”
Section: Discussionmentioning
confidence: 97%
“…& M.A. Curtis) Rostovzev, even various genera of a host family ( Wa t e r h o u s e a n d B r o t h e r s 1 9 8 1 ; L e b e d a a n d Widrlechner 2003; Runge and Thines 2009, 2012Kitner et al 2015). Thus, it is necessary that new occurrences of Peronospora are investigated not only by the recording of new hosts but also by morphological and phylogenetic characteristics.…”
Section: Introductionmentioning
confidence: 96%